Hollow silica particles and compositions containing the same
Patent Information
- Application Number
- JP2026064032
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-04-09
- Filing Date
- 2026-04-08
- Publication Date
- 2026-10-22
AI Technical Summary
【0021】 本発明の一側面に係る中空シリカは、顕著に優れた均一性及びシリカ壁材の特性を有し、高機能性精密化学及びバイオ素材用途において優れた有用性を有することができる。
Smart Images

Figure 2026170876000001_ABST
Abstract
Description
[Technical Field]
[0001] This invention relates to hollow silica particles and compositions containing them. [Background technology]
[0002] Hollow silica particles are widely used in various industrial fields due to their unique hollow structure, chemical stability, high specific surface area, and low density. They are used as core materials in application areas such as drug delivery systems, catalysts, adsorbents, sensors, optical materials, films, thermal barriers, and cosmetics.
[0003] The hollow structure offers flexibility in adjusting the physical and chemical properties for application fields, and can impart new functionalities that conventional silica particles cannot provide. Specifically, hollow silica particles offer low density and a large specific surface area due to their hollow structure, and the particle size, wall thickness, and pore size can be precisely adjusted according to synthesis conditions, thus having broad applicability in various application fields. Furthermore, the surface of silica particles can be replaced with various chemical functional groups, thereby adjusting hydrophilicity or hydrophobicity, and also imparting biocompatibility. For example, in pharmaceutical or cosmetic compositions, the internal space of hollow silica particles can function as a storage space for drugs or physiologically active substances, and the external surface of the silica particles can acquire functionality by binding with functional groups or ligands suitable for the application.
[0004] However, introducing a hollow structure has the drawback of requiring a complex manufacturing process. Furthermore, even minute changes in the manufacturing process can easily alter particle size, wall thickness, and pore structure, limiting the ability to uniformly maintain and precisely control the physicochemical properties of hollow silica particles.
[0005] Along with the versatility of silica particles and the advantages possessed by the hollow structure, the application possibilities of hollow silica particles are increasingly expanding, and their usefulness is particularly growing in the integrated fields of environmentally friendly fine chemical materials and biomaterials. Accordingly, there is a demand for the development of high-quality hollow silica that can satisfy various requirements, ranging from conventional application fields that leverage physicochemical properties derived from the hollow structure to uses of high-performance fine chemicals or biomaterials. [Prior Art Documents] [Patent Documents]
[0006] [Patent Document 1] Japanese Registered Patent No. 7218651 [Summary of the Invention] [Problem to be Solved by the Invention]
[0007] One aspect of the present invention is to provide hollow silica having excellent physicochemical properties in various application fields.
[0008] One aspect of the present invention is to provide hollow silica that has low refractive index, low dielectric constant, and excellent abrasion resistance, and can form a coating film having uniform low-refractive and low-reflective optical properties when applied to a coating film. Means for Solving the Problem
[0009] The hollow silica particles according to an embodiment of the present invention are characterized by having Type IV adsorption-desorption characteristics in nitrogen isothermal adsorption-desorption, having a closure point at a relative pressure of 0.75 to 0.85, and having a particle dispersion index represented by the following Formula 1 of 1.7 or more.
[0010] [Formula 1] D V / FWHM V (In Formula 1, D V means the volume average particle diameter measured by dynamic light scattering analysis, and FWHM V means the full width at half maximum of the hollow silica particles in the volume particle size distribution graph.)
[0011] In the hollow silica particles according to one embodiment, the hollow silica particles may have a hollow dispersion index represented by the following Formula 2 of 1.5 or more.
[0012] [Formula 2] D h / FWHM h (In Formula 2, D h means the average diameter of the hollows obtained from a transmission electron microscope image, and FWHM h means the full width at half maximum in the hollow size distribution graph.)
[0013] In the hollow silica particles according to one embodiment, the ratio of the volume average particle diameter (D V ) to the number average particle diameter (D n ) of the hollow silica particles (D V / D n ) may satisfy 1 to 1.3.
[0014] In the hollow silica particles according to one embodiment, the BET specific surface area of the hollow silica particles may be 50 to 100 m 2 / g, and the pore volume may be 0.4 to 0.6 cm 3 / g.
[0015] In the hollow silica particles according to one embodiment, the average pore diameter of the hollow silica particles calculated by the BJH method on a nitrogen desorption basis may be 20 to 30 nm.
[0016] In the hollow silica particles according to one embodiment, in the graph of the log-scale pore diameter by BJH and the differential value of the pore volume with respect to the log-scale pore diameter of the hollow silica particles, a single peak may be present in the pore diameter range of 2 to 50 nm.
[0017] In the hollow silica particles according to one embodiment, the volume average particle diameter (D V ) of the hollow silica particles is 60 to 90 nm, and the average hollow diameter (D h ) may be 50 to 80 nm.
[0018] In one embodiment of hollow silica particles, the absolute value of the zeta potential of the hollow silica particles may be 40 mV or more.
[0019] A dispersion according to one embodiment of the present invention contains the hollow silica particles described above.
[0020] An optical film according to one embodiment of the present invention contains the hollow silica particles described above. [Effects of the Invention]
[0021] One aspect of the present invention involves hollow silica, which possesses remarkably excellent uniformity and silica wall material properties, and can be highly useful in high-performance fine chemical and biomaterial applications.
[0022] One aspect of the present invention involves hollow silica, which has low refractive index, low dielectric constant, and excellent wear resistance, and because the physical properties of the particles are highly uniform, a coating film containing hollow silica can have optical properties of uniform low reflectivity and low refractive index. [Brief explanation of the drawing]
[0023] [Figure 1] ~ [Figure 2] This figure shows a TEM image of hollow silica according to one embodiment. [Figure 3] This figure shows the nitrogen adsorption / desorption isotherm of hollow silica according to one embodiment. [Figure 4] This figure shows the pore distribution diagram of hollow silica according to one embodiment. [Modes for carrying out the invention]
[0024] Unless otherwise defined, the technical and scientific terms used herein have the meanings that would normally be understood by a person with ordinary skill in the art to which this invention pertains. Descriptions of prior art functions and configurations that could obscure the essence of the invention are omitted in the following description and accompanying drawings.
[0025] The embodiments described herein may be modified in various other forms, and the art relating to one embodiment is not limited to the embodiments described below. Furthermore, the embodiment of one embodiment is provided to further fully illustrate the invention to a person of average skill in the art.
[0026] Furthermore, the singular form used in the specification and the attached claims may be intended to include plural forms unless otherwise indicated in the context.
[0027] Furthermore, unless otherwise specified, the units used herein are based on weight. For example, units of % or ratio mean weight percent or weight ratio, and weight percent means the weight percent of any component in the total composition unless otherwise specified.
[0028] Furthermore, the numerical ranges used herein include lower limits, upper limits, and all values within those ranges, increments logically derived from the form and width of the defined range, all doubly limited values, and all possible combinations of upper and lower limits of numerical ranges limited in different forms. Unless otherwise specifically defined in the specification of the present invention, values outside the numerical range that may occur due to experimental error or rounding of values are also included in the defined numerical range.
[0029] In this specification, the term "includes" is an open-ended statement equivalent to expressions such as "equips," "contains," "has," or "characterizes," and does not exclude elements, materials, or processes that are not additionally listed. Furthermore, the term "substantially includes" means that it includes the components described in the claims as essential components, but may further include non-essential components that do not substantially affect the effect.
[0030] In this specification, unless otherwise specified, the average particle size may be measured by a dynamic light scattering analyzer, and the average particle size refers to the volume-based average particle size.
[0031] The present invention will be described in detail below using various embodiments or examples of the present invention. It should be noted that each embodiment or example described herein is not merely limited to a single embodiment or example, but can also be combined with other embodiments or examples. Therefore, the claims cited in the claims are merely illustrative examples of embodiments, and the technical idea of the present invention should not be interpreted solely in combination with the cited claims; various combinations with claims are also included within the scope of the technical idea of the present invention.
[0032] One aspect of the present invention is a hollow silica particle that has Type IV adsorption / desorption characteristics in isothermal nitrogen adsorption / desorption, has a closing point at a relative pressure (P / P0) of 0.75 to 0.85, and has a particle dispersion index of 1.7 or higher, as shown in the following formula 1.
[0033] [Formula 1] D V / FWHM V In formula 1, D V This refers to volume-average particle size determined by dynamic light scattering analysis, FWHM. V This represents the full width at half maximum (FWHM) of hollow silica particles in the volume particle size distribution graph.
[0034] The hollow silica particles, due to their hollow structure, have low density and high specific surface area, making them highly applicable as general heat shields and optical materials. Furthermore, possessing Type IV nitrogen adsorption / desorption properties based on the IUPAC definition and having the particle dispersion index described above, they exhibit excellent properties for solute adsorption, storage, and release, making them highly applicable as supports and storage media such as drug delivery systems, catalyst supports, and adsorbents.
[0035] Specifically, the hollow silica particles can have closure points at relative pressures (P / P0) of 0.78 to 0.85, specifically 0.80 to 0.85. These closure points are physical properties that indicate the characteristics of the mesopores of the hollow silica particles and are related to the size distribution of the mesopores, the connectivity of the mesopores, and the surface characteristics of the mesopores. Therefore, these closure points can express pore characteristics that cannot be expressed by combinations of pore volume, pore size, and specific surface area of the pores.
[0036] Specifically, the particle dispersion index expressed in Equation 1 above may be 1.75 or higher, 1.8 or higher, or 1.85 or higher, and not limited to being 10 or lower, 9 or lower, or 5 or lower. Specifically, the particle dispersion index expressed in Equation 1 above may be 1.7 to 10, 1.75 to 9, 1.8 to 5, or 1.85 to 5.
[0037] The BET specific surface area of the hollow silica particles is 40 to 120 m². 2 / g, 50-100m 2 / g, 60-90m 2 / g, specifically 65-85mg 2 / g is acceptable.
[0038] The pore volume of the hollow silica particles is 0.3 to 0.7 cm³. 3 / g, 0.35~0.65cm 3 / g, 0.4~0.6cm 3 / g, specifically 0.45~0.55cm 3 / g is acceptable.
[0039] The average pore diameter of the hollow silica particles, calculated by the nitrogen desorption-based BJH method, may be 15-35 nm, 18-32 nm, specifically 20-30 nm. The BET specific surface area, pore volume, and average pore size may be measured by BET analysis using nitrogen adsorption and desorption. The hollow silica particles, containing mesopores and the pore structure described above, may be effective in adsorbing and storing solutes without degradation of heat shielding or optical properties due to the hollow structure. To give a non-limiting example, the catalyst supported in the hollow silica particles allows reactants to rapidly contact the catalyst particles with low diffusion resistance, and the products generated by the catalytic reaction are rapidly discharged to the outside, thus maintaining excellent catalytic activity even at relatively high space velocities.
[0040] According to one embodiment, in a log-scale graph of pore diameter and pore volume calculated by BJH (Barrett-Joyner-Halenda) for the hollow silica particles, a single peak can be observed in the pore diameter range of 2 to 50 nm. Specifically, in a graph plotted with the log-scale pore diameter (w) calculated by BJH in nitrogen adsorption / desorption experiments of the hollow silica particles as the x-axis and the derivative of the pore volume with respect to the log-scale pore diameter (dV / dlog(w)) as the y-axis, the hollow silica particles exhibit a single peak in the mesopore diameter range, i.e., in the diameter range of 2 to 50 nm. In other words, the presence of a single peak in the log(w) vs dV / dlog(w) graph indicates that very uniform mesopores have developed in the silica wall.
[0041] According to one embodiment, the hollow silica particles are 50-100 m 2 BET specific surface area and 0.4~0.6 cm² per g 3 It can have a stomata volume of / g.
[0042] According to one embodiment, the hollow silica particles may have a hollow dispersion index of 1.5 or higher, as shown in the following formula 2.
[0043] [Formula 2] Dh / FWHM h In formula 2, D h This refers to the average diameter of the hollow space obtained from the transmission electron microscope image, FWHM. h This represents the maximum full width at half maximum in the hollow size distribution graph. Specifically, it represents the average diameter (D) of the hollow. h ) and FWHM h This refers to the FWHM obtained from the average value of the hollow diameter and the diameter distribution map obtained by TEM image analysis for any 100 particles.
[0044] Specifically, the hollow dispersion index expressed in Equation 2 above may be 1.6 or higher, 1.7 or higher, 1.8 or higher, 1.9 or higher, 2.0 or higher, 2.1 or higher, or 2.2 or higher, and not limited to being 10 or lower, 9 or lower, 8 or lower, or 5 or lower. Specifically, the hollow dispersion index expressed in Equation 2 above may be 1.5 to 10, 1.6 to 9, 1.8 to 8, 2.0 to 5, or 2.2 to 5.
[0045] By satisfying particle dispersion index and hollow dispersion index of 1.7 or higher and 1.5 or higher, preferably 1.8 or higher and 2.0 or higher, respectively, hollow silica particles can have a uniform hollowness ratio for each individual particle, and can preferably have excellent utility in optical materials where it is necessary to maintain a uniform refractive index in minute regions over a large area.
[0046] The volume fraction of the hollow silica particles, relative to the total volume of the hollow silica particles, may be 45-75%, 48-70%, or specifically 50-65%.
[0047] The volume-average diameter (D) of the hollow silica particles V The average diameter of the hollow (D) may be 50-150 nm, 55-130 nm, 58-120 nm, 60-100 nm, or 60-90 nm. h The wavelengths may be 40-100nm, 45-95nm, 50-90nm, 55-90nm, 60-85nm, or 65-85nm.
[0048] According to one embodiment, the volume average diameter (D V The average diameter of the hollow space is 60-90 nm, and the average diameter of the hollow space is D h ) may be 50-80 nm, specifically the volume average diameter (D V The average diameter of the hollow space is 65-90 nm, and the average diameter of the hollow space is D h ) is 50-80 nm, or volume average diameter (D V The average diameter of the hollow space is 70-85 nm, and the average diameter of the hollow space is D h ) may be between 55 and 75 nm.
[0049] According to one embodiment, the volume-average particle size (D) of the hollow silica particles V ) and number-average particle size (D n ) ratio (D V / D n ) may satisfy 1 to 1.3. The number average particle size (D) of the hollow silica particles. n ) refers to the number-average particle size calculated by dynamic light scattering analysis. The ratio (D V / D n The ratio (D) is an index that indicates the particle size dispersibility of hollow silica particles. In the case of general hollow silica particles, it is known that not only do they exhibit polydispersity, but the hollow dispersion index, as mentioned above, is also non-uniform. However, hollow silica particles according to one embodiment can have a particle size distribution close to monodispersity. Specifically, the ratio (D) V / D n ) may be 1 to 1.25 or 1 to 1.2.
[0050] According to one embodiment, the absolute value of the zeta potential of the hollow silica particles may be 40 mV or more. Specifically, the hollow silica particles may have a negative zeta potential, and may have an absolute value of 45 mV or more or 50 mV or more, and not limited to having an absolute value of 70 mV or less.
[0051] Another aspect of the present invention is to provide a dispersion containing hollow silica particles as described above. The dispersion may be a dispersion in a polar solvent, for example, an aqueous dispersion, an alcohol dispersion, or a dispersion in an organic solvent, and the aqueous dispersion may further contain a solvent that is miscible with water.
[0052] The aforementioned miscible solvents may be alcohol-based solvents, acetate-based solvents, carboxylic acid-based solvents, ketone-based solvents, amine-based solvents, amide-based solvents, or ether-based solvents. Specific examples include, but are not limited to, acetic acid, methanol, ethanol, isopropanol, ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, butanediol, glycerol, diethoxyamine, ethylene acetate, dimethylformamide, formic acid, N-methylpyrrolidone, and propylene glycol monomethyl ether acetate.
[0053] Another aspect of the present invention provides an article containing hollow silica particles as described above. The article may be one selected from drug delivery systems, catalysts, adsorbents, sensors, optical materials, films, heat shields, and cosmetics. The article containing the hollow silica particles can provide superior performance in terms of physical properties depending on the required purpose, as the hollow silica particles are uniformly dispersed.
[0054] In one embodiment, the article may be an optical film. Optical films require uniform and excellent optical properties (refractive index, light transmittance, reflectance, etc.). While conventional hollow silica particles are effective in improving optical properties, they have the disadvantage of poor uniformity of optical properties across the entire optical film, especially over large areas, due to the lack of uniformity in the physicochemical properties of the particles.
[0055] However, the optical film according to the present invention, by containing the hollow silica particles of the present invention as described above, can have uniform and excellent optical properties throughout the entire film. Specifically, the optical film has the physical property of having uniform hollow silica particles, and because they are uniformly dispersed, optical properties such as refractive index can be uniform over a large area, providing a superior optical effect in optical films where uniformity is required. Furthermore, the uniform dispersion of hollow silica particles suppresses stress concentration within the film, improving durability against external forces, which can increase scratch resistance and impact resistance. In addition, due to the uniform hollow distribution, the optical film can have superior mechanical and chemical properties compared to conventional optical films, such as excellent heat insulation performance and photothermal stability.
[0056] Specifically, the optical film is not particularly limited as long as it adjusts the optical properties such as reflection, transmission, refraction, and dispersion of light. Non-limiting examples include anti-reflective or low-reflection films, low-refractive-index films, polarizing films, prism films, diffusion films, phase difference films, brightness-enhancing films, transmission-adjusting films, and the like.
[0057] The following will provide specific examples of embodiments and experimental cases. However, the embodiments and experimental cases described below are merely illustrative examples, and the technology described herein is not limited to them.
[0058] <Example 1> 1) Preparation of the first solution 4,273g of pure water was added to a glass reactor equipped with a stirrer, and 71g of sodium aluminate (Na2O 41% by weight, Al2O3 49% by weight) and 4g of sodium hydroxide were added and mixed. The mixture was then heated and maintained at 60°C to produce the first solution.
[0059] 2) Preparation of the second solution In a separate container, 17,165 g of pure water and 487 g of sodium silicate aqueous solution (Na2O 9.5% by weight, SiO2 29% by weight) were mixed and stirred at room temperature (25±5℃) to prepare the second solution.
[0060] 3) Production of hollow silica aqueous sol A core particle aqueous sol was produced by gradually adding 5,652 g of the second solution to the first solution, which was being kept heated, over a period of 4 hours. Subsequently, while heating and maintaining the core particle aqueous sol at 70°C, 12,000 g of the second solution was gradually added over a period of 4 hours to form a shell around the core particles and produce a silica aqueous sol. 910 g of hydrochloric acid (Mita Pure Chemical Industries, 36%) was added to the silica aqueous sol and stirred for 1 hour, followed by a 24-hour maturation treatment to produce a hollow silica aqueous sol with voids inside the particles.
[0061] 4) Production of hollow silica dispersion Next, the solution was concentrated to 4,200 g using an ultrafiltration membrane with a molecular weight cutoff of 300,000 Daltons. The dilution and concentration process was repeated with pure water to remove impurities, yielding a concentrated hollow silica aqueous sol with an electrical conductivity of 68 μs / cm. Diisopropylamine was added to the concentrated hollow silica aqueous sol to adjust the pH to 11, and then it was placed in a high-pressure reactor and subjected to hydrothermal synthesis treatment at 160°C for 6 hours to form a dense shell with increased density. Subsequently, a hollow silica dispersion was produced in which hollow silica particles were dispersed by repeatedly concentrating and diluting using an ultrafiltration membrane with a molecular weight cutoff of 300,000 Daltons to remove impurities.
[0062] <Example 2> In Example 1, a hollow silica dispersion was produced in the same manner as in Example 1, except that in step 1) the first solution production step, 5,402 g of pure water, 90 g of sodium aluminate, and 5 g of sodium hydroxide were mixed, and in step 2) the second solution production step, 16,036 g of pure water and 455 g of aqueous sodium silicate solution were added.
[0063] <Example 3> In Example 1, a hollow silica dispersion was produced in the same manner as in Example 1, except that in step 1) the production of the first solution, 3,604 g of pure water, 60 g of sodium aluminate, and 3 g of sodium hydroxide were mixed, and in step 2) the production of the second solution, 17,834 g of pure water and 506 g of aqueous sodium silicate solution were added.
[0064] <Example 4> In Example 1, a hollow silica dispersion was produced in the same manner as in Example 1, except that the temperature of the first solution was heated and maintained at 70°C in step 1) first solution production and step 3) hollow silica aqueous sol production, and the core particle aqueous sol was heated and maintained at 80°C in step 3) hollow silica aqueous sol production.
[0065] <Comparative Example 1> In Example 1, a hollow silica dispersion was produced in the same manner as in Example 1, except that in step 3) hollow silica aqueous sol production, the mixture was heated and maintained at 98°C while adding the second solution all at once to the first solution which was heated and maintained at 98°C, and the resulting mixture was heated and maintained at 98°C to produce a silica aqueous sol.
[0066] <Comparative Example 2> In Example 1, a hollow silica dispersion was produced in the same manner as in Example 1, except that in step 3) hollow silica aqueous sol production, the mixture was heated and maintained at 70°C while adding the second solution all at once to the first solution which was heated and maintained at 70°C, and the resulting mixture was heated and maintained at 70°C to produce a silica aqueous sol.
[0067] <Evaluation of hollow silica particles> (Experimental Example 1) Measurement of Hollow Size As shown in Figures 1 and 2, after obtaining transmission electron microscope images of hollow silica particles, the hollow diameter of any 100 hollow silica particles was measured to obtain the average hollow diameter and the FWHM in the hollow size distribution graph. h The following measurements were taken, and the results are shown in Table 1 below.
[0068] (Experimental Example 2) Dynamic Light Scattering (DLS) Dynamic light scattering analysis was performed using a light scattering spectrometer (Litesizer DLS700, Anton Paar) equipped with a 658 nm wavelength semiconductor laser in a laser Doppler system. After replacing the solvent from water to ethanol, the concentration of hollow silica particles in the dispersion was adjusted to 0.1 wt% and used as the analytical sample. Scattered light was detected by a detector (Avalanche photodiode, APD) positioned at 90° to the incident light source, and the particle distribution was calculated using the CONTIN routine. Table 1 below shows the calculated volume-average particle size (D) of the hollow silica particles. V ), number average particle diameter (D n ), FWHM V The zeta potential values were also recorded.
[0069] (Experimental Example 3) Analysis of Porous Properties To understand the specific surface area and pore structure of hollow silica particles, nitrogen adsorption experiments were conducted using 3Flex (Micromeritics). Before nitrogen adsorption analysis, the samples were pretreated at 150°C under vacuum for 8 hours, and then nitrogen adsorption and desorption were performed. The BET (Brunauer-Emmett-Teller) specific surface area, pore volume, and average pore size (diameter) were calculated, and the results are shown in Table 1 below. Figure 3 shows the nitrogen adsorption / desorption BET isotherms, and Figure 4 shows the pore distribution diagram.
[0070] [Table 1] JPEG2026170876000002.jpg56170
[0071] Referring to Table 1 above, it was confirmed that the hollow silica particles in the hollow silica dispersion according to the examples exhibited Type IV behavior in isothermal adsorption / desorption of nitrogen, and that there was a closure point at a relative pressure of a minimum of 0.78 and a maximum of 0.83, and simultaneously D h / FWHM hIt was confirmed that the value was 2 or greater, specifically 2.5 or greater. For example, referring to Figure 3, it was shown that the hollow silica of Example 1 has a closure point at a relative pressure of 0.83, exhibiting typical Type IV BET adsorption-desorption behavior. This result means that the hollow silica of Example 1 has very uniform mesopores, but the pore openings are narrower than the internal pores, suggesting that diffusion of substances is not easy. As a result, even when the hollow silica of the example is combined with polymers that form a continuous phase to form a composition and manufactured as an article, the hollow structure can be preserved very well within the article, and the remarkable effects of the hollow structure can be exerted.
[0072] Furthermore, in the pore characteristic analysis, the average pore diameter of the hollow silica particles in the examples was 25.7 nm to 33.2 nm, and the average pore volume was 0.47 to 0.54 cm³. 3 It was confirmed that the values were per gram, and the average pore diameter of the hollow silica particles in the comparative example was 29.4 nm to 31.2 nm, and the average pore volume was 0.62 to 0.89 cm³. 3 It was / g.
[0073] In the pore characteristic analysis, the log-scale pore diameter and the differential value of volume with respect to pore diameter graphs using BJH for the hollow silica particles of the examples showed only a single peak located in the pore diameter range of 25 nm to 40 nm. For example, referring to Figure 4, the hollow silica of Example 1 was shown to have a single peak at approximately 31 nm. On the other hand, the hollow silica of Comparative Examples 1 and 2 showed peaks located in the pore diameter range of 10 nm to 20 nm and peaks located in the pore diameter range of 20 nm to 35 nm simultaneously.
[0074] The above results suggest that the hollow silica produced in the examples has uniform colloidal properties, hollow properties, and porosity properties.
[0075] <Coating film evaluation> Low-reflection coating solutions were prepared containing the hollow silica dispersions produced in the above examples and comparative examples, and the physical properties of the coating films produced from these coating solutions were evaluated.
[0076] Specifically, 60 g of siloxane resin diluted with propylene glycol methyl ether at a solid content concentration of 50% by weight was mixed with 90 g of concentrated hollow silica aqueous sol and 850 g of propylene glycol methyl ether, which were dispersed in propylene glycol methyl ether at a concentration of 0.3% by weight according to the examples and comparative examples. A low-reflection coating liquid with a solid content concentration of 3% by weight was prepared, and a coating film was manufactured using the method described in the test example below. After that, the physical properties were evaluated.
[0077] First, a low-reflection coating solution was applied to a microscope slide (LK LAB KOREA, microscope slides) using a spin coating method, and then heat-cured at 120°C for 30 minutes to obtain a specimen with a low-reflection coating film measuring 20 cm wide, 20 cm long, and 100 nm thick.
[0078] The reflectance, haze, transmittance, and refractive index were measured at 10 random locations on the manufactured specimens, and the mean and standard deviation were calculated. Reflectance was measured using a Konica Minolta CM-3600A spectrophotometer, and haze and transmittance were measured using a Murakami Color Technology Laboratory HM-150 haze meter. Separately, the refractive index was measured using an ellipsometer after forming a 1-micron thick coating film on a silicon wafer, and the evaluation results are shown in Table 2 below.
[0079] [Table 2] JPEG2026170876000003.jpg44170
[0080] Referring to Table 2 above, the coating films containing hollow silica according to the examples showed good results in reflectance, haze, transmittance, and refractive index, and in particular, it was confirmed that they had uniform optical properties over the entire area. On the other hand, in the case of Comparative Examples 1 and 2, non-uniform optical properties were observed over the entire area.
Claims
1. Hollow silica particles characterized by having Type IV adsorption / desorption characteristics in isothermal nitrogen adsorption / desorption, having a closure point at a relative pressure of 0.75 to 0.85, and having a particle dispersion index of 1.7 or higher, as expressed by the following formula 1. [Formula 1] D V / FWHM V (In formula 1, D V This refers to the volume-average particle size determined by dynamic light scattering analysis, FWHM. V This represents the maximum full width at half maximum of hollow silica particles in the volume particle size distribution graph.
2. The hollow silica particles according to claim 1, wherein the hollow dispersion index expressed by the following formula 2 is 1.5 or greater. [Formula 2] D h / FWHM h (In formula 2, D h This refers to the average diameter of the hollow space obtained from the transmission electron microscope image, FWHM h This represents the maximum full width at half maximum in the hollow size distribution graph.
3. The volume average particle diameter (D of the hollow silica particles V ) and the number average particle diameter (D n ) (the ratio D V / D n ) of which satisfies 1 to 1.3, the hollow silica particles according to claim 1.
4. The BET specific surface area of the hollow silica particles is 50 to 100 m². 2 The gas content is per gram, and the stomatal volume is 0.4–0.6 cm³. 3 Hollow silica particles according to claim 1, wherein the particle size is / g.
5. The hollow silica particles according to claim 1, wherein the average pore diameter of the hollow silica particles calculated by the nitrogen desorption-based BJH method is 20 to 30 nm.
6. The hollow silica particle according to claim 1, wherein the graph of the log-scale pore diameter and the differential value of the pore volume with respect to the log-scale pore diameter, calculated by BJH, has a single peak in the range of pore diameter from 2 to 50 nm.
7. The volume-average particle size (D) of the hollow silica particles V The average diameter of the hollow space is 60-90 nm, and the average diameter of the hollow space is D h The hollow silica particles according to claim 1, wherein the wavelength is 50 to 80 nm.
8. The hollow silica particle according to claim 1, wherein the absolute value of the zeta potential of the hollow silica particle is 40 mV or more.
9. A dispersion containing hollow silica particles according to any one of claims 1 to 8.
10. An optical film comprising hollow silica particles according to any one of claims 1 to 8.
Citation Information
Patent Citations
Hollow silica particles, dispersions of hollow silica particles, and films
JP7218651B2